Overweight/obesity-related transcriptomic signature as a correlate of clinical outcome, immune microenvironment, and treatment response in hepatocellular carcinoma - Feng, Ning-Ning; Du, Xi-Yue; Zhang, Yue-Shan; Jiao, Zhi-Kai; Wu, Xiao-Hui; Yang, Bao-Ming (Frontiers in Endocrinology, 2023)
The pandemic of overweight and obesity (quantified by body mass index (BMI) ≥ 25) has rapidly raised the patient number of non-alcoholic fatty hepatocellular carcinoma (HCC), and several clinical trials have shown that BMI is associated with the prognosis of HCC. However, whether overweight is an independent prognostic factor is arguable and the role of overweight-related metabolisms in the progression of HCC is scarcely known. In the present study, clinical information, mRNA expression profile, and genomic data were downloaded from The Cancer Genome Atlas (TCGA) as a training cohort (TCGA-HCC) for identification of overweight-related transcriptome. Overweight-associated transcriptome was mainly involved in metabolic processes, noticeably, markedly correlated with prognosis and TME of HCC. Afterwards, machine learning and Cox regression analysis were conducted for construction of the overweight-associated genes (OAGs) signature. Kaplan-Meier curve, receiver operating characteristic (ROC) curve, and Cox regression analysis was performed to assess the prognostic value of OAGs signature. A novel established OAGs signature divided patients into high and low OAGs score groups with distinct prognosis (median overall survival (OS): 24.87 months vs. 83.51 months, p < 0.0001), and the values of area under ROC curve (AUC) in predicting 1-, 2-, 3-, and 4-year OS were 0.81, 0.80, 0.83, and 0.85, respectively. Besides, OAGs score was independent from clinical features and also exhibited good ability of prognosis prediction in ICGC-LIHC-JP cohort and GSE54236 dataset. Expectedly, OAGs score was also highly correlated with metabolic processes, especially oxidative-related signaling pathways. Furthermore, abundant enrichment of chemokines, receptors, MHC molecules, and other immunomodulators as well as PD-L1/PD-1 expression among patients with high OAGs score indicated that those might have better response to immunotherapy. However, probably exclusion of T cells from infiltrating tumors resulting in lower infiltration of effective T cells would restrict immunotherapeutic effects. In addition, OAGs score was significantly associated with the response of sorafenib and TACE treatment. Overall, this study comprehensively disclosed the relationship between BIM-guided transcriptome and HCC. Moreover, OAGs signature had the potential clinical applications in future to promote clinical management and precision medicine of HCC.